III Italian Consensus Conference on Malignant Mesothelioma of the Pleura. Epidemiology, Public Health and Occupational Medicine related issues - Magnani, Corrado; Bianchi, Claudio; Chellini, Elisabetta; Consonni, Dario; Fubini, Bice; Gennaro, Valerio; Marinaccio, Alessandro; Menegozzo, Massimo; Mirabelli, Dario; Merler, Enzo; Merletti, Franco; Musti, Marina; et al. (La Medicina del Lavoro, 2015)
The III Italian Consensus Conference on Pleural Mesothelioma (MM) convened on January 29th 2015. This report presents the conclusions of the ‘Epidemiology, Public Health and Occupational Medicine’ section. MM incidence in 2011 in Italy was 3.64 per 100,000 person/years in men and 1.32 in women. Incidence trends are starting to level off. Ten percent of cases are due to non-occupational exposure. Incidence among women is very high in Italy, because of both non-occupational and occupational exposure. The removal of asbestos in place is proceeding slowly, with remaining exposure. Recent literature confirms the causal role of chrysotile. Fibrous fluoro-edenite was classified as carcinogenic by IARC (Group 1) on the basis of MM data. A specific type (MWCNT-7) of Carbon Nanotubes was classified 2B. For pleural MM, after about 45 years since first exposure, the incidence trend slowed down; with more studies needed. Cumulative exposure is a proxy of the relevant exposure, but does not allow to distinguish if duration or intensity may possibly play a prominent role, neither to evaluate the temporal sequence of exposures. Studies showed that duration and intensity are independent determinants of MM. Blood related MM are less than 2.5%. The role of BAP1 germline mutations is limited to the BAP1 cancer syndrome, but negligible for sporadic cases. Correct MM diagnosis is baseline; guidelines agree on the importance of the tumor gross appearance and of the hematoxylin-eosin-based histology. Immunohistochemical markers contribute to diagnostic confirmation: the selection depends on morphology, location, and differential diagnosis. The WG suggested that 1) General Cancer Registries and ReNaM Regional Operational Centres (COR) interact and systematically compare MM cases; 2) ReNaM should report results presenting the diagnostic certainty codes and the diagnostic basis, separately; 3) General Cancer Registries and COR should interact with pathologists to assure the up-to-date methodology; 4) Necroscopy should be practiced for validation. Expert referral centres could contribute to the definition of uncertain cases. Health surveillance should aim to all asbestos effects. No diagnostic test is recommended for MM screening. Health surveillance should provide information on risks, medical perspective, and smoking cessation. The economic burden associated to MM was estimated in 250,000 Euro per case.